Kinerja Keuangan Bank Syariah sebagai Implikasi atas Konsentrasi Kepemilikan - Dian Nirmala Dewi; Artie Arditha Rachman; Endang Asliana (Politeknik Negeri Lampung, 2021)
This study aims to examine the effect of ownership concentration and type of share ownership on the financial performance of Islamic banks in Indonesia. The sample used is Islamic commercial banks recorded in Indonesian Islamic Banking Statistics, with a study period of five years, from 2014 to 2018. Regression testing involves financial performance (ROA, ROE, and NPL) as the dependent variable; ownership concentration (K) and ownership type (INST, GOV, FAM and FOR) as independent variables; and some control variables, such as CAR, size, leverage, and company age. Data collected shows that all of Islamic Banks in Indonesia have concentrated ownership, therefore that factor should be omitted from independent variables. Based on hypothesis testing, we find that financial performance of Islamic Banks in Indonesia are not influenced by it’s ownership type.